2022
DOI: 10.1186/s13071-022-05186-x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, season, and latitude influence development-related phenotypes of Philippine Aedes aegypti (Linnaeus): Implications for dengue control amidst global warming

Abstract: Background Dengue is endemic in the Philippines. Aedes aegypti is the primary vector. This study aimed to determine the hatching behavior and viability of Ae. aegypti first-generation (F1) eggs when exposed to temperature and photoperiod regimes under laboratory conditions. Methods Parental eggs were collected from selected highland and lowland sites in the Philippine big islands (Luzon, Visayas, and Mindanao) during the wet (2017–2018) and dry (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The Philippines continues to experience the health burden caused by high dengue cases, ranking number one in Asia with 17,630 deaths last March 2021 ( Edillo et al., 2015 , 2022 ; Ong et al., 2022 ). The persistent high cases annually prompted the Philippine government to establish the National Dengue Prevention and Control Program with vector surveillance and management as one of the key targets ( Dengue Prevention and Control Program | Department of Health website, n.d. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Philippines continues to experience the health burden caused by high dengue cases, ranking number one in Asia with 17,630 deaths last March 2021 ( Edillo et al., 2015 , 2022 ; Ong et al., 2022 ). The persistent high cases annually prompted the Philippine government to establish the National Dengue Prevention and Control Program with vector surveillance and management as one of the key targets ( Dengue Prevention and Control Program | Department of Health website, n.d. ).…”
Section: Introductionmentioning
confidence: 99%
“…The persistent high cases annually prompted the Philippine government to establish the National Dengue Prevention and Control Program with vector surveillance and management as one of the key targets ( Dengue Prevention and Control Program | Department of Health website, n.d. ). Aedes aegypti mosquito is the primary vector of Dengue in the Philippines owing to its adaptability in changing environments ( Edillo et al., 2022 ). To mitigate infections, recommendations for vector management including the reduction of breeding sites, and improvement of water systems have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…ROs were highest at 25 degrees Celsius in the wet season and at 18 degrees Celsius in the dry season. Furthermore, the study noted that the incidence of the dengue-causing mosquito phenotype was found to be highest at 18 degrees Celsius and present even at 38 degrees Celsius in both seasons, suggesting larval adaptation to global warming [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of dengue in the Philippines increased from 37,101 in 2006 to 118,868 in 2010 [ 10 ]. Significant outbreaks since 2012 recorded 187,000 dengue cases and as many as 270,00 cases between January and August 2019 [ 11 ], ranking the country fourth out of ten in ASEAN [ 12 ]. The degradation of the environment due to urbanization, an increase in population, poor waste disposal strategies, changes in weather conditions, and poor surveillance of mosquito breeding sites are among the factors that contribute to the rise in dengue cases in the country [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%